Adipose stem cells-derived exosomes modified gelatin sponge promotes bone regeneration - Li, Gen; Zhang, Yin; Wu, Jiezhou; Yang, Renhao; Sun, Qi; Xu, Yidong; Wang, Bo; Cai, Ming; Xu, Yang; Zhuang, Chengyu; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Large bone defects resulting from trauma and diseases still a great challenge for the surgeons. Exosomes modified tissue engineering scaffolds are one of the promising cell-free approach for repairing the defects. Despite extensive knowledge of the variety kinds of exosomes promote tissue regeneration, little is known of the effect and mechanism for the adipose stem cells-derived exosomes (ADSCs-Exos) on bone defect repair. This study aimed to explore whether ADSCs-Exos and ADSCs-Exos modified tissue engineering scaffold promotes bone defects repair. Material/Methods: ADSCs-Exos were isolated and identified by transmission electron microscopy (TEM), nanoparticle tracking analysis, and western blot. Rat bone marrow mesenchymal stem cells (BMSCs) were exposed to ADSCs-Exos. The CCK-8 assay, scratch wound assay, alkaline phosphatase activity assay, and alizarin red staining were used to evaluate the proliferation, migration, and osteogenic differentiation of BMSCs. Subsequently, a bio-scaffold, ADSCs-Exos modified gelatin sponge/polydopamine scaffold (GS-PDA-Exos), were prepared. After characterized by scanning electron microscopy and exosomes release assay, the repair effect of the GS-PDA-Exos scaffold on BMSCs and bone defects was evaluated in vitro and in vivo. Results: The diameter of ADSCs-exos is around 122.1 nm and high expressed exosome-specific markers CD9 and CD63. ADSCs-Exos promote the proliferation migration and osteogenic differentiation of BMSCs. ADSCs-Exos was combined with gelatin sponge (GS) by polydopamine（PDA）coating and released slowly. After exposed to the GS-PDA-Exos scaffold, BMSCs have more calcium nodules with osteoinductive medium and higher expression the mRNA of osteogenic related genes compared with other groups. The quantitative analysis of all micro-CT parameters showed that GS-PDA-Exos scaffold promote new bone formed in the femur defect model in vivo and confirmed by histological analysis. Conclusions: This study demonstrates the repair efficacy of ADSCs-Exos in bone defects, ADSCs-Exos modified scaffold showing a huge potential in the treatment of large bone defects.